Two new troglobiont Pygmarrhopalites species of the principalis group (Collembola: Arrhopalitidae) from the West Caucasus - Vargovitsh, Robert S. (Zootaxa, 2017)
Springtails of the principalis-group of the genus Pygmarrhopalites from the W Caucasian caves in Abkhazia are described: Pygmarrhopalites dbari sp. nov. from Psyrtskha Cave in Novy Afon and Pygmarrhopalites kovali sp. nov. from caves of Tsebelda Karst Massif. They differ from epigean relatives mainly by troglomorphies: reduced pigmentation, elongated appendages and modified foot complex. These new species as well as a great portion of endemic Caucasian speleofauna have highly restricted distribution and require protection. A new record of Arrhopalites abchasicus Vargovitsh, 2013 in Novoafonskaya Cave is added.